2016
DOI: 10.1186/s40623-016-0527-9
|View full text |Cite
|
Sign up to set email alerts
|

Systematic difference between first-motion and waveform-inversion solutions for shallow offshore earthquakes due to a low-angle dipping slab

Abstract: Systematic difference between first-motion and waveform-inversion solutions for shallow offshore earthquakes was examined by using the seismograms of the 2016 Off Mie (Mw 5.8) earthquake occurred at a depth of 14 km southeast off of the Kii peninsula, central Japan. Observed seismograms illustrated first arrivals with an apparent velocity of 7.2 km/s, which is faster than crustal P waves. The apparent velocity and polarization pattern of the first arrivals were reproduced by a finite-difference method simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Hereafter, shallow VLFE is referred to as SVLFE. Activity of SVLFEs may provide us with information on the frictional conditions around shallower parts of the plate boundaries (e.g., Saffer & Wallace, 2015 a conventional analysis using a one-dimensional (1-D) velocity structure is not expected to be accurate due to offshore lateral heterogeneities related to the subducting plate and accretionary prism (e.g., Takemura et al, 2016Takemura et al, , 2018, especially since the accretionary prism has a significant influence on seismic wave propagation for periods around predominant periods of SVLFE signals (e.g., Furumura et al, 2008;Shapiro et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Hereafter, shallow VLFE is referred to as SVLFE. Activity of SVLFEs may provide us with information on the frictional conditions around shallower parts of the plate boundaries (e.g., Saffer & Wallace, 2015 a conventional analysis using a one-dimensional (1-D) velocity structure is not expected to be accurate due to offshore lateral heterogeneities related to the subducting plate and accretionary prism (e.g., Takemura et al, 2016Takemura et al, , 2018, especially since the accretionary prism has a significant influence on seismic wave propagation for periods around predominant periods of SVLFE signals (e.g., Furumura et al, 2008;Shapiro et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, strong horizontal heterogeneities of seismic wave velocities due to plate subduction could affect the precision of determining the hypocenter locations. Takemura et al (2016) showed that an accurate 3D velocity model reflecting the plate subduction is necessary to explain the spatial distributions of P-wave first motion polarities observed for this earthquake. Therefore, a velocity model reflecting the horizontal heterogeneities is crucial for precise determination of hypocenters.…”
Section: Introductionmentioning
confidence: 99%
“…due to 3-D velocity structure (e.g. Nakamura et al, 2016;Takemura et al, 2016). We therefore assume that a layer average provides meaningful information in lieu of more detailed depth analysis, comment on some depth-dependence below, and furthermore assume that any mislocation bias in the catalog will be temporally stationary.…”
Section: Catalog Analysismentioning
confidence: 99%